Beispiel Nr: 14
$ \text{Gegeben: } \text{Nullstellen: } x_1\qquad x_2 \\ \text{Formefaktor: } a \\ \text{Gesucht: faktorisierte Form } y=a(x-x_1)(x-x_2) \\ \text{Allgemeine Form }y=ax^2+bx+c \\ \\ \text{Nullstellen - Faktorisierte Form}\\ \textbf{Gegeben:} \\ P(-1/0)\qquad Q(-1/0) \\\\ \\ \textbf{Rechnung:} \\ P(-1/0)\qquad Q(-1/0) \qquad a=2 \\ \text{Formfaktor a und Nullstellen in die faktorisierte Form einsetzen}\\ y=a(x-x_1)(x-x_2)\\ y=2(x+1)(x+1)\\ y=2(x^2+x \cdot 1 +1\cdot x +1\cdot 1 )\\ y=2(x^2 +2 x+1) \\ y= 2x^2+4x+2 $